2022
DOI: 10.3390/ijerph19042162
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Long-Term Care Insurance Certification in Japan: A Scoping Review

Abstract: This study aimed to review evidence on future long-term care associated with pre-existing factors among community-dwelling Japanese older adults. We systematically searched cohort and nested case–control studies published between 2000 and 2019 that assessed long-term care certification using the PubMed, CINAHL, and EMBASE databases. The relationship between long-term care insurance information and risk factors was investigated. The protocol was registered with the Open Science Framework. We extracted 91 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 97 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…Besides these factors, some potential covariates confound the association of interest, and their effects were not adjusted, which is a limitation of this study. For example, the systematic review by Tanaka et al describes physical conditions (e.g., motor function, physical frailty, sarcopenia) and social factors (social participation, social support, social capital, and social frailty) as some of the most frequently reported risk factors for the certification of need for long-term care 44 . These items related to physical conditions and social factors are not obtained in general health checkups in Japan and were also not obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these factors, some potential covariates confound the association of interest, and their effects were not adjusted, which is a limitation of this study. For example, the systematic review by Tanaka et al describes physical conditions (e.g., motor function, physical frailty, sarcopenia) and social factors (social participation, social support, social capital, and social frailty) as some of the most frequently reported risk factors for the certification of need for long-term care 44 . These items related to physical conditions and social factors are not obtained in general health checkups in Japan and were also not obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review reported that risk factors for LTC certification included physical function [ 35 ]. Previous studies suggested that the benefits of Tai Chi Yuttari exercise included improvements in physical function such as improvement in balance ability (evaluated by standing on one leg) and flexibility (evaluated by bending forward) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies that treat a presence of LTCI certification as an indicator of frailty and disability, regardless of support or care needs levels. 45 Further research is needed into the relationship between LTCI certification and frailty and disability.…”
Section: Study Limitationsmentioning
confidence: 99%